Una propuesta de enseñanza de la probabilidad basada en aplicaciones financieras para estudiantes de ciencias administrativas, económicas y contables - Diaz Osorio., Miguel Andrés (Universidad Antonio Nariño, 2023)
One of the difficulties observed in students of economic sciences is the absence of correlation between the objects of the subjects of probability and financial mathematics as well as the topics that are developed in these courses, this could be verified through a diagnostic study elaborated to give validity to the present investigation, focused on measuring the perception of the student body of administrative sciences towards business decision-making in contingent environments. This study was carried out in seven universities, six private and one public in Bogotá.